Study on instability and damage of a loess slope under strong ground motion by numerical simulation. Issue 152 (January 2022) - Chang, Chaoyu; Bo, Jingshan; Qi, WenHao; Qiao, Feng; Peng, Da
Abstract: The instability and damage of loess slopes under strong ground motion can be a complicated process, involving sliding, translation, and rotation, which makes the discrete element method as a suitable theory to simulate such a process. Therefore, in this study, the particle flow code (PFC) is developed to simulate the instability and damage process of the loess landslide under strong motion. Based on field investigations and laboratory tests, the detailed identification of mesoscopic parameter was calibrated, and a 2D model was established. The results show that the slope surface tends to amplify the ground motion, resulting in the strong vibration of the soil on the slope surface. The slope shoulder is the position with the largest amplification coefficient of seismic acceleration, which is the key to the instability and failure of the slope. And, under the seismic force, the tensile failure firstly occurs in the slope upper part, and then the accumulation failure occurs in the lower part, finally a shear outlet is formed. Accordingly, high-frequency component of the Fourier spectrum increases with the slope failure. This study highlights the gradual increase in the difference between the first principal stress and the third principal stress, which destroys the inherent cohesive cements between particles, which is the main cause of slope failure under strong motion. Highlights: The particle flow code (PFC) is developed to simulate the instability and damage process of the loess landslide under strong motion. The slope surface tends to amplify the ground motion, resulting in the strong vibration of the soil on the slope surface. The slope shoulder is the position with the largest amplification coefficient of seismic acceleration. Under the seismic force, the tensile failure firstly occurs in the slope upper part, and then the accumulation failure occurs in the lower part,  finally a shear outlet is formed.